1999
DOI: 10.1007/s000110050383
|View full text |Cite
|
Sign up to set email alerts
|

The effect of in vitro activation and platelet interaction on the CD9 distribution and adhesion properties of human eosinophils

Abstract: Our findings, that CD9 expression on eosinophils is dynamically regulated, support our previous suggestion that CD9 may be a useful activity marker and that platelet interaction acts on eosinophil adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…50 Several authors have found decreasing CD9 expression in eosinophils on activation, a phenomenon probably caused by release/shedding of soluble forms of CD9 and not caused by intracellular degradation. 51,52 It is likely that this CD9 expression decrease could be due to secretion of CD9 1 eosinophil exosomes, and for this reason, we have observed an increase in CD9 1 exosomes after eotaxin eosinophil stimulation.…”
Section: Discussionmentioning
confidence: 76%
“…50 Several authors have found decreasing CD9 expression in eosinophils on activation, a phenomenon probably caused by release/shedding of soluble forms of CD9 and not caused by intracellular degradation. 51,52 It is likely that this CD9 expression decrease could be due to secretion of CD9 1 eosinophil exosomes, and for this reason, we have observed an increase in CD9 1 exosomes after eotaxin eosinophil stimulation.…”
Section: Discussionmentioning
confidence: 76%
“…Arterial thrombosis is a major pathogenic mechanism in acute coronary syndromes [127,128] and involves cross‐talk among platelets, leukocytes and endothelial cells [129]. A plethora of stimulatory or inhibitory agonists may influence the formation of platelet–leukocyte aggregates which may facilitate leukocyte tethering, rolling and migration and enhance thrombin generation [130,131]. Leukocyte‐released is one of the factors that could induce platelet–leukocyte aggregation [132].…”
Section: Oxidative Stress and Arterial Thrombosismentioning
confidence: 99%
“…To confirm that the collagen preparation does not activate leukocytes, platelet-poor blood was prepared by using Percoll (Amersham Pharmacia Biotech) as described previously 18 but omitting the step of red blood cell lysis. The lower layer (granulocytes and red blood cells) was resuspended with HEPES-buffered saline containing 1.25 mmol/L CaCl 2 and centrifuged at 800g for 10 minutes.…”
Section: Platelet-poor Blood Preparationmentioning
confidence: 99%
“…For example, plateletmonocyte conjugation may enhance thrombin generation, and conjugated platelets may facilitate leukocyte rolling, adhesion, and migration in vivo 17 and in vitro. 18 Previous studies have mostly been performed on isolated cells 19,20 and have thus neglected the possibly important influences of red blood cells and plasma components on these interactions. Studies in whole blood 21 were conducted in the presence of citrate, ie, with subphysiological calcium concentrations, which may alter platelet responses.…”
mentioning
confidence: 99%